First occurrence of Nemobiinae crickets in the Lesser Antilles (Orthoptera, Grylloidea, Trigonidiidae), with the descriptions of three new species - Desutter-Grandcolas, Laure; Hugel, Sylvain (Zootaxa, 2016)
The occurrence of Nemobiinae crickets (Grylloidea, Trigonidiidae) in the Lesser Antilles is attested here for the first time, by the descriptions of three new species of Absonemobius Desutter-Grandcolas, 1993 from Guadeloupe, St. Lucia and St. Vincent: Absonemobius septentrion n. sp., Absonemobius lucensis n. sp. and Absonemobius vincenti n. sp., and the discovery of Hygronemobius Hebard, 1913 in Guadeloupe. The generic attribution of several nemobiine species described from the Caribbean and from Southern Central America are also reviewed: Nemobius elegans Otte, 2006 from Costa Rica and Pteronemobius sanaco Otte & Perez-Gelabert, 2009 described from Belize are transferred to Hygronemobius; Hygronemobius darienicus Hebard, 1913 described from Panama is transferred to Absonemobius Desutter-Grandcolas, 1993; Hygronemobius epia Otte & Perez-Gelabert, 2009 does not belong to Hygronemobius, but is temporarily kept in this genus as incertae sedis.